2001
DOI: 10.1182/blood.v98.4.972
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus (EBV) reactivation is a frequent event after allogeneic stem cell transplantation (SCT) and quantitatively predicts EBV-lymphoproliferative disease following T-cell–depleted SCT

Abstract: Reactivation of the Epstein-Barr virus (EBV)after

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
302
1
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(316 citation statements)
references
References 62 publications
8
302
1
5
Order By: Relevance
“…Measuring EBV DNA has since been studied extensively and is now an indispensable tool for controlling PTLD. This method is used not only for diagnosis, but also for disease prediction [33,34,[58][59][60], therapeutic efficacy estimation [61,62], and prevention [63][64][65][66]. There has been debate regarding which specimen(s) should be used to identify PTLD.…”
Section: Post-transplant Lymphoproliferative Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Measuring EBV DNA has since been studied extensively and is now an indispensable tool for controlling PTLD. This method is used not only for diagnosis, but also for disease prediction [33,34,[58][59][60], therapeutic efficacy estimation [61,62], and prevention [63][64][65][66]. There has been debate regarding which specimen(s) should be used to identify PTLD.…”
Section: Post-transplant Lymphoproliferative Disordermentioning
confidence: 99%
“…Recent studies have used plasma or serum because they are readily obtained and handled. Several studies reported that quantifying cell-free EBV DNA predicted the development of PTLD [59,68,69]. However, serum or plasma samples lack cell-associated virus and therefore plasma loads are not correlated with PBMC values [70].…”
Section: Post-transplant Lymphoproliferative Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported a significantly increased EBV load at the time of diagnosis of post-transplant lymphoproliferative disease, up to 4log 10 higher than in control groups [Bai et al, 1997;Riddler et al, 1994;Rowe et al, 1997;Meerbach et al, 2001]. A rapid increase in peripheral blood EBV DNA load diagnosed and predicted posttransplant lymphoproliferative disease [Stevens et al, 2001a;Van Esser et al, 2001a;Orentas et al, 2003].…”
Section: Ebv Serostatusmentioning
confidence: 99%
“…Frequent molecular monitoring of the EBV load and anti-CD20 antibody therapy for cases at high risk have been suggested. [12][13][14] To further determine the incidence, outcome, risk profiles and clinical characteristics of EBV reactivations and PTLD in the post transplant period, we here performed a retrospective study in all 854 patients who received allogeneic SCT between January 1999 and June 2007 in the University Hospital of Hamburg, Germany, and performed further characterization of the 11 cases with EBV-associated PTLD and of the 15 cases with EBV reactivation.…”
Section: Introductionmentioning
confidence: 99%